2019
DOI: 10.1111/jpn.13217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oat decortication on chemical composition, in vitro digestibility and in situ degradability

Abstract: The effect of decortication on chemical composition and degradability characteristics of four Danish oat varieties was investigated. Effective degradability (ED) and post‐ruminal disappearance (PRD) were measured by in situ and mobile bag techniques respectively. Decorticated oat showed higher (p = .01) concentrations of crude protein (CP; 134 vs. 108 g/kg DM) and crude fat (71.6 vs. 53.1 g/kg DM) and a higher (p = .001) organic matter digestibility (OMD; 888 vs. 703 g/kg OM) than oat. The content of total fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Therefore, the FA composition in hull compared with whole oat explains the effect of decortication on FA composition of diets containing undecorticated oat. In agreement with the present findings, Panah et al (2020b) also reported an increased FA content in decorticated oat. Therefore, decortication of oat is a tool to increase the concentration of FA in the ration.…”
Section: Intakesupporting
confidence: 93%
“…Therefore, the FA composition in hull compared with whole oat explains the effect of decortication on FA composition of diets containing undecorticated oat. In agreement with the present findings, Panah et al (2020b) also reported an increased FA content in decorticated oat. Therefore, decortication of oat is a tool to increase the concentration of FA in the ration.…”
Section: Intakesupporting
confidence: 93%
“…Decorticating of grains is a practical tool for increasing the digestible energy content of dairy cow diets without altering the forage-to-concentrate ratios (Yang et al, 1997;Wang et al, 2017). Decortication resulted in the expected changes in composition and in vitro digestibility (Panah et al, 2019). The composition of the removed oat hull showed that hulls are low in CP and high in NDF.…”
Section: Processing Of Oatmentioning
confidence: 99%
“…Although the in situ digestibility of lost particles was previously assumed to be similar to the particles remaining in the bag (Hvelplund and Weisbjerg, 2000), the interpretation of in situ observations in the case of oat grains must be done with caution. Particle loss for DM and CP is substantial in oat (Panah et al, 2019). Therefore, due to the methodology of in situ evaluation, the in vivo ruminal starch digestibility cannot be explained by reduced DM and CP particle loss in situ due to toasting.…”
Section: Digestibility Of Other Nutrientsmentioning
confidence: 99%
“…Although there was an effect on α-tocopherol and α-tocotrienol content in oat due to decortication and toasting; the effect on overall intake of α-tocopherol was negligible, thus, in the discussion the overall fate of tocopherols across treatments throughout the gastrointestinal tract is discussed. Results for ruminal and post ruminal digestibility of protein ( Panah et al., 2020c ), amino acids ( Panah et al., 2020a ) and fatty acids ( Panah et al., 2020b ) have previously been presented and discussed.…”
Section: Discussionmentioning
confidence: 99%